Les illustrations en pleine page du cartulaire du XIIe siècle (ms 210 d’Avranches), problèmes d’interprétation et sources textuelles - Jacques Le Maho (Tabularia)
The three large images that adorn folios 4v, 19v and 25v of the 12th-century cartulary have already been extensively studied and commented upon and continue to raise numerous problems of interpretation. On the assumption that these drawings are partly based on texts independent of the cartulary, the present study aims to try to identify these sources. In the case of the illustration on folio 4v, the investigation carried out through a series of historical and literary texts leads to the conclusion that the palace of Saint Aubert is probably inspired by the description of a hydraulic clock in the image of the celestial city. The illustration on folio 19v, dedicated to the Montois reform of Richard I, is based on the Introductio monachorum. The illustration on folio 25v, depicting two miracles that occurred on the Mount, seems to have two main sources: a life of William the Long Sword and the late eleventh-century book of Miracula. One of the two miracles is not associated with any of the charters in the cartulary, which raises the question of why the image was included in this collection.